2016
DOI: 10.1093/ndt/gfv457
|View full text |Cite
|
Sign up to set email alerts
|

Urinary biomarker incorporation into the renal angina index early in intensive care unit admission optimizes acute kidney injury prediction in critically ill children: a prospective cohort study

Abstract: We have now prospectively validated the RAI as a functional risk stratification methodology in a heterogeneous group of critically ill patients, providing context to direct measurement of novel urinary biomarkers and improving the prediction of severe persistent AKI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
59
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(69 citation statements)
references
References 49 publications
9
59
1
Order By: Relevance
“…Our results were agreed with study Shina Menon et al 2016 [10], which state that approximately one in three patients (32.6%) was RA+ within the irst 12h of PICU admission. These patients had a higher prevalence of sepsis.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results were agreed with study Shina Menon et al 2016 [10], which state that approximately one in three patients (32.6%) was RA+ within the irst 12h of PICU admission. These patients had a higher prevalence of sepsis.…”
Section: Discussionsupporting
confidence: 93%
“…Our results was agreed with study of Shina Menon et al 2016 [10], which stated that there was statistically signi icant increase in serum creatinine and renal angina ful illment (RAI+) (P-value < 0.001).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The renal angina index (RAI) is used for pediatric cohorts instead of RA to evaluate the risk for developing AKI by establishing point values [47, 48]. Clinical studies confirmed that a combined use of AKI biomarkers with RAI could improve the predictive value of the biomarkers for AKI [49]. Therefore, to a certain extent, this approach may be considerably potent for early prediction of AKI.…”
Section: Discussionmentioning
confidence: 99%
“…The RAI combines validated clinical risk factors (ICU admission, solid organ or stem cell transplant, mechanical ventilation, and vasopressor need) with evidence for decreased kidney function (increases in serum creatinine or degrees of fluid accumulation) to stratify patients at risk for subsequent severe AKI. Importantly, the incorporation of urinary biomarkers further improves the predictive ability of the RAI (26). In a prospective study of 184 children admitted to the pediatric ICU, a positive RAI (score ≥8) was present in 33% of patients at day 0 and predicted day 3 AKI with an AUC of 0.80.…”
Section: Identify Patients Who Are At Risk For Aki Post-injury Earlymentioning
confidence: 99%